2020
DOI: 10.1016/j.ekir.2020.01.001
|View full text |Cite
|
Sign up to set email alerts
|

Preemptive Treatment With Elbasvir and Grazoprevir for Hepatitis C–Viremic Donor to Uninfected Recipient Kidney Transplantation

Abstract: Introduction: Long wait times for kidney transplants have prompted investigation into strategies to decrease the discarding of potentially viable organs. Recent reports suggest that kidneys from hepatitis C virus (HCV)Àinfected donors may be transplanted into HCV-naive donors followed by direct-acting antiviral therapy.Methods: This was a pilot clinical trial to transplant kidneys from HCV-infected donors into HCV-naive recipients with preemptive use of elbasvir and grazoprevir for 12 weeks. The primary outcom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
0
16
2
Order By: Relevance
“…Similarly, Sise et al demonstrated that prophylactic DAA therapy can shorten the duration of viremia by providing the first dose of a 12‐week DAA course in the operating room. In this cohort, seven of eight patients had detectable viral loads post‐operatively with only one patient remaining detectable after post‐operative day 7 11 …”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, Sise et al demonstrated that prophylactic DAA therapy can shorten the duration of viremia by providing the first dose of a 12‐week DAA course in the operating room. In this cohort, seven of eight patients had detectable viral loads post‐operatively with only one patient remaining detectable after post‐operative day 7 11 …”
Section: Discussionmentioning
confidence: 92%
“…Published literature has consistently demonstrated near 100% certainty of donor transmission of HCV in the absence of prophylactic DAAs 4 . However, early or prophylactic treatment with DAA has been shown to greatly reduce the incidence of viremia and decrease detectable viral loads 2,9‐11 . Here we examine the effect of the cumbersome authorization processes as it relates to pharmacy benefit plans and the timing of DAA treatment in our cohort of uninfected kidney recipients transplanted with HCV‐positive donor kidneys.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, larger case series have confirmed these results. 5,9,12,17,18,[25][26][27][28][29][30][31][32] Despite the published outcomes in clinical studies, the development of safe and effective strategies to utilize DHCV NAT+ organs is challenging. 10 Safe transplantation requires coordination to ensure universal posttransplant testing, access to DAAs for viremic patients, and appropriate monitoring to ensure compliance and viral clearance.…”
Section: Discussionmentioning
confidence: 99%
“…including groups which achieved high levels of viral clearance with shorter courses of DAA treatment, although several patients required retreatment as a result of viral resistance. 12,[15][16][17][18] Despite this rapidly changing landscape, knowledge and comfort with transplantation of DHCV+ organs has not been systematically assessed. Clinical care and decision-making for transplant providers is more complex for DHCV NAT+ kidneys, due to potential concerns about medical and psychosocial risks for the recipients.…”
Section: Introductionmentioning
confidence: 99%
“…Regimens provided with safety and efficacy towards all HCV genotypes, even in patients with advanced CKD, should be adopted. Overall, a total of 201 kidney transplants were collected ( Table 3 ); as listed in Table 3 and Table 4 , the majority of the reports had high efficacy and safety [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ]. However, some studies were externally funded, and this is a source of bias [ 48 ].…”
Section: Kidney Transplant From Hcv-positive/nat-positive (Hcv Rna-positive) Donors In Naïve Recipientsmentioning
confidence: 99%